(untitled) (KYAMC Journal, 2017)
Background: Obstructive jaundice can be caused by malignant or benign lesions. The treatment for these conditions is biliary decompression either by surgery or by endoscopic methods. Objectives: The aim of this study was to evaluate the diagnostic and therapeutic role of ERCP with its success and limitations in the management of obstructive jaundice. Methods: This study was carried out in the depertment of General Surgery & hepato-biliary surgery in Bangabandhu Sheikh Mujib Medical University during 1st January, 2012 to 30th June,2012. Results: The study included 60 patients (male, 38, female,22), mean age 45 years(range, 21-70 years). Commonest malignant cause of obstructive jaundice was Carcinoma of the pancreas 27% followed by, cholangiocarcinoma 15%, and periampullary carcinoma 8%. Bile duct stone 32% was the commonest benign cause followed by papillary stenosis 13% and round warm in biliary tree 5%. Stenting were done in 42% of patients and success rate was 92%. Biopsy were taken for diagnosis in 8% for papillary tumours. Stone extraction were done in 32% of patients for CBD stone and success rate was >94%. Warm extraction were done in 5% and sphincterotomy in 11% of patients for papillary stenosis where success rate was 100%. ERCP could not be performed due to stenosis of duodenum in 1.66% of patients, complete papillary obstruction in 3.33%, papillary position abnormality in 3.33% and endoscopically ampulla not found in 5% of patients. The commonest post ERCP complication was acute pancreatitis that was 5%. Other complications include bleeding in 3.33%, perforation in 1.66% and acute cholangitis in 3.33% cases. Conclusion: Despite its associated limitations and complication, ERCP is a reliable method in treating obstructive jaundice for most of the benign conditions and stenting as a palliative measure & tissue diagnosis in malignant obstruction. In this study the success rate is acceptable for ERCP in the management of obstructive jaundice. KYAMC Journal Vol. 8, No.-1, Jul 2017, Page 38-42